Multiscale Computational Model Reveals Nerve Response in a Mouse Model for Temporal Interference Brain Stimulation - Gomez-Tames, Jose; Asai, Akihiro; Hirata, Akimasa (Frontiers in Neuroscience, 2021)
There has been a growing interest in the noninvasive stimulation of specific brain tissues, while reducing unintended stimulation in surrounding regions, for the medical treatment of brain disorders. Traditional methods for noninvasive brain stimulation, such as transcranial direct current stimulation or transcranial magnetic stimulation, can stimulate brain regions, but they also simultaneously stimulate the brain and non-brain regions that lie between the target and the stimulation site of the source. Temporal interference (TI) stimulation has been suggested to selectively stimulate brain regions by superposing two alternating currents with slightly different frequencies injected through electrodes attached to the scalp. Previous studies have reported promising results for TI applied to the motor area in mice, but the mechanisms are yet to be clarified. As computational techniques can help reveal different aspects of TI, in this study, we computationally investigated TI stimulation using a multiscale model that computes the generated interference current pattern effects in a neural cortical model of a mouse head. The results indicated that the threshold increased with the carrier frequency and that the beat frequency did not influence the threshold. It was also found that the intensity ratio between the alternating currents changed the location of the responding nerve, which is in agreement with previous experiments. Moreover, particular characteristics of the envelope were investigated to predict the stimulation region intuitively. It was found that regions with high modulation depth (|maximum| – |minimum| values of the envelope) and low minimum envelope (near zero) corresponded with the activation region obtained via neural computation.